2006
DOI: 10.1002/jcp.20761
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Kv and MaxiK currents associated with increased MRP1 expression in small cell lung carcinoma

Abstract: Regulatory volume decrease and exocrine secretion studies suggest a functional relationship between K+ and organic anion efflux. To test the hypothesis that the expression of K+ channels and MRP1 is reciprocally related, we employed the patch clamp and RT-PCR techniques on weakly (H69) and strongly MRP1-expressing (H69AR) small cell lung cancer cells. H69AR cells do not express the time- and voltage-dependent delayed rectifying K+ current (Kv) reported earlier in H69 cells and confirmed here. About 80% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…In addition to the potential therapeutic impact of KCNJ2/Kir2.1, our studies shed light on the mechanisms by which KCNJ2/Kir2.1 mediates MDR in SCLC. Several studies have confirmed that MRP1/ABCC1 is highly expressed in H69AR cells [ 30 , 31 ], and may be closely related to chemoresistance in SCLC [ 22 ]. Enyeart et al showed that K + channels, including KCNJ2/Kir2.1, might function with MRP1/ABCC1 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the potential therapeutic impact of KCNJ2/Kir2.1, our studies shed light on the mechanisms by which KCNJ2/Kir2.1 mediates MDR in SCLC. Several studies have confirmed that MRP1/ABCC1 is highly expressed in H69AR cells [ 30 , 31 ], and may be closely related to chemoresistance in SCLC [ 22 ]. Enyeart et al showed that K + channels, including KCNJ2/Kir2.1, might function with MRP1/ABCC1 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the Leanza group demonstrated, in several cancer cell lines, a similar relationship between reduced expression of Kv1.1 and Kv1.3 and decreased sensitivity to drugs, provoking mitochondrial-induced apoptotic death [106]. Another study conducted using small cell lung carcinoma cells demonstrated a relation between K + channel expression profile and drug resistance [107]. More precisely, authors demonstrated that the expression level of BKCa and Kv channels was inversely correlated to the MRP1 expression levels.…”
Section: Potassium Channelsmentioning
confidence: 99%